Modified atmosphere package for apple ‘Bravo de Esmolfe’ - Rocha, A.M.C.N. (2004)
Apple Bravo de Esmolfe original from the parish of Esmolfe is cultivated in specific regions of Portugal. This cultivar of medium to low production requires very low temperatures, but it is extremely sensitive to frost. The aim of this work was to evaluate the influence of modified atmosphere on the quality of apple (cv. Bravo de Esmolfe) during cold storage. Apples packed in modified atmosphere lost less weight, presented better colour, and preserved better firmness than fruits stored in air.